Radiolucent Jaw Lesions: Imaging Approach - Kumar, Jyoti; Vanagundi, Rajesh; Manchanda, Alpana; Mohanty, Sujata; Meher, Ravi (Indian Journal of Radiology and Imaging, 2021)
Jaw lesions are a wide array of benign, malignant, and locally aggressive lesions. On radiography, they can appear radiolucent, mixed, or radioopaque. The imaging appearances of radiolucent jaw lesions are markedly overlapping. The role of the radiologist is to formulate a narrow differential diagnosis based on imaging characteristics and aid appropriate management decisions. The aim of this pictorial review is to familiarize the reader with the imaging approach to radiolucent jaw lesions, which form the bulk of jaw lesions in clinical practice.
Keywords: computed tomography; magnetic resonance imaging; orthopantomogram; radiolucent jaw lesions